Metalliferous soils: chemical attributes in different phytophysiognomies of the Serra Sul, Serra dos Carajás, Pará, Brazil - Vasconcelos, Josemar Moreira; Silva Júnior, Mário Lopes da; Ruivo, Maria de Lourdes Pinheiro; Schaefer, Carlos Ernesto G. R.; Rodrigues, Possidônio Guimarães; Souza, Gisele Teixeira de; Nascimento, Dryelle de Nazaré Oliveira do; Bezerra, Kelly Cristina Alves; Dias, Yan Nunes (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2017)
The different phytophysiognomies that occur in formations rich in iron-Plateau canga ferrífera on national forest of Carajás, known as Serra Sul, located in the south west of the State of Pará, have peculiar vegetation rich in endemics, and currently are subjected to pressure from mining, however are little studied. In this sense, the objective of this study was to identify the chemical attributes that correlate in different physiognomies of canga. Soil sampling was carried out in depth ranging from 0.05 to 0.20 cm because the canga hematítica form large blocks of hard minerals, which varies in different phytophysiognomies: campo rupestre aberto (CR.AB), campo rupestre arbustivo (CR.AR), capão florestal (CF), mata de encosta (ME), mata de buritizais (MB) and capão florestal lacustre (CFL).Was rated the pH, organic carbon, total nitrogen, available phosphorus, potassium, calcium, magnesium, sodium, aluminum, exchangeable cationic exchange capacity, base saturation, total bases and saturation of aluminum. The results were analyzed through uni and multivariate statistical. The soils of the physiognomies studied showed high acidity and very low levels of phosphorus, potassium, magnesium and calcium. Multivariate analysis allowed a clear distinction between four distinct groups associated with the fertility of the soil: 1) CR.AR, CF, CFL; 2) ME; 3) MB and 4) CR.AB.
Keywords: Canga ferrífera; Soil fertility; Rupestrian ferruginous fields; Canga soils